(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: Hydatid disease is an endemic disease that affects many regions of the world. Even surgeons in nonendemic regions face the condition, so they should be familiar with the best way to treat it. Aim: This study aims to determine the effectiveness new trocar-cannula system, the Palanivelu Hydatid System (PHS), a new, safe approach for laparoscopic treatment of hepatic hydatid disease. Place and Duration: In the surgical department of Lady Reading Hospital, Peshawar for the duration from Jan 2019 to December 2021. Methods: The Palanivelu Hydatid System was used to perform laparoscopic surgery on 40 patients of hepatic hydatid disease. The trocar-cannula system technique was utilised as well as the method of surgery was elaborated in detailed. A total of 40 patients were included in this study. Results: The maximum of patients complained of pain and the majority had one cyst only. The liver's right lobe was most frequently affected. Four patients had bilateral cysts. In 77.8% of cases, the Palanivelu Hydatid System was used to merely remove the hydatid cyst. Due to the large size of the cysts, which nearly filled the entire left liver lobe in 11.2% of cases, a left lobectomy was performed. Omentoplasty was used to treat the residual cavity. A follow-up period was 1-year on average recurrence was seen in one patient only. Conclusion: For the treatment of hepatic hydatid disease, we advise Palanivelu Hydatid System. We have discovered that it works best for avoiding spillage, completing trans-cystic fenestration, removing the contents of hydatid cysts and handling with cyst-biliary communications.